Relationship of Midwife's Knowledge Level about HIV/AIDS with Stigma to Pregnant Women with HIV/AIDS in Primary Health Service of Banyumas Regency - Wilda Salsabiela (Placentum: Jurnal Ilmiah Kesehatan dan Aplikasinya, 2023)
Background: The HIV/AIDS Situation Analysis conducted by the Banyumas Regency Health Office in September – October 2021 shows that HIV/AIDS cases are increasing rapidly. The high number of HIV/AIDS cases can lead to negative opinions or stigma attached to people living with HIV/AIDS (PLWHA). High knowledge of midwives can be a good behavior in preventing HIV transmission.. Objective[WU1] : This research aims to analyze the correlation between the level of knowledge of midwives concerning HIV/AIDS and the stigma of pregnant women with HIV/AIDS in primary health care centers in Banyumas Regency. Independent variable in this study was the midwives' knowledge of HIV/AIDS and the dependent variable in this study is the stigma of midwives in pregnant women with HIV/AIDS Method[WU2] : This study was descriptive analysis with cross-sectional research design. [WU3] The research subjects were midwives who had never attended HIV counselor training at the Medical Support Service Health Center in Banyumas Regency with a total of 61 respondents[WU4]  which is obtained from the withdrawal sampling technique using cluster random sampling where according to Sugiyono's 2017 book that cluster random sampling is obtained by the formula for the number of respondents per cluster divided by the total number of respondents multiplied by the sample. The instrument used the HIV-KQ-18 questionnaire to measure the level of knowledge and the SHASS questionnaire to measure stigma attitudes. The analysis uses the Spearman rank correlation test. Results : A total of (14.80%) level of knowledge is sufficient and (1.60%) high stigma. There is no significant relationship between the level of knowledge of midwives and the stigma of pregnant women with HIV/AIDS in primary health services in Banyumas district. Conclusion[WU6] : The knowledge of midwives about HIV/AIDS still needs to be improved. Efforts need to be made in relation to the stigma of midwives against PLWHA and educational institutions can add workshops with experts, Health Office, health services,Keywords:HIV, Midwife Stigma, Knowledge, Pregnant women